2010
DOI: 10.1051/limn/2010013
|View full text |Cite
|
Sign up to set email alerts
|

Reliable sample sizes for estimating similarity among macroinvertebrate assemblages in tropical streams

Abstract: -Studies in tropical streams are relatively few, and one of the still-unresolved methodological issues is sample size. Adequate sample size for temperate streams cannot be extrapolated for tropical sites, because of the differences in species richness and the proportions of rare species. We evaluated reliable sample size for estimation of resemblance among samples of macroinvertebrate assemblages inhabiting riffles of tropical streams, using the autosimilarity approach. Sample sizes were much larger than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…We conclude that randomization analytical procedures, such as multiple-run Monte Carlo analyses, as recommended by Flotemersch et al (2010) and Schneck and Melo (2010) are useful for estimating sufficient sampling effort for assessing vertebrate, macroinvertebrate, and diatom taxa richness in rivers.…”
Section: Discussionmentioning
confidence: 97%
“…We conclude that randomization analytical procedures, such as multiple-run Monte Carlo analyses, as recommended by Flotemersch et al (2010) and Schneck and Melo (2010) are useful for estimating sufficient sampling effort for assessing vertebrate, macroinvertebrate, and diatom taxa richness in rivers.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is still necessary to test family-level in a biomonitoring program for streams in the whole region, considering there is substantial difference of biota among the biomes. Finally, few studies in Latin America have dealt with developing and testing of other important aspects of biomonitoring protocols, such as sampling procedures and mesh sizes (Buss and Borges 2008), sample size (Schneck and Melo 2010), subsampling methods (Oliveira et al 2011a;Ligeiro et al 2013a), and taxonomic sufficiency (e.g., Melo 2005;Buss and Vitorino 2010).…”
Section: Developing Large-scale Biomonitoring Programs Elsewhere-latimentioning
confidence: 99%
“…Others also have demonstrated that fixed-count size can affect richness estimates (e.g., McCord et al, 2007;Oliveira et al, 2011), the separation between sites or groups (e.g., Cao et al, 2002a;Schneck and Melo, 2010), and performance of MMIs (e.g., Doberstein et al, 2000) and O/E indices (e.g., Nichols et al, 2006;Ostermiller and Hawkins, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We expect that BC yielded higher CS than JC because BC provided proportional abundance data that are less variable than the pure richness data of JC, which is sensitive to rare taxa. Therefore, we also expected that CS (JC) needed a greater fixedcount size to achieve asymptotes than CS (BC) (Schneck and Melo, 2010).…”
Section: Discussionmentioning
confidence: 99%